Nhận diện tính năng mới của thư viện thông minh trong giáo dục - Đậu, Mạnh Hoàn (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
The Industrial Revolution 4.0 has a great impact on the entire economic, political - social life of human beings including educational activities. One of its characteristics is that automation will gradually replace manual labor and the integration of people with machines in many activities will replace manual labor. Library profession and library work are also in the same trend. The digital library system in general has rapidly developed into a smart library to meet the development of science and technology timely, and thereby meet new tasks in education and training activities of the period 4.0.     Smart library or the 4.0 generation library is known for the many outstanding capabilities that digital libraries cannot have. It helps educational activities in schools to be fully exploited and diversified in educational activities to improve quality. In this article presents some new features of smart library through technology to serve teaching and learning in the Industry 4.0 era.